(NsORO^INSKAQ QRMARKA(B. (Nm(B. (Np(B. (NmUSORGSKOGOs (NLIBERETTOs - (Nn(B. (N{UMSKAQs ((NmOSKWAs (NmUZYKAs)
(NpREDNAZNA^EN DLQ POSETITELEJ OPERNOGO TEATRA(B,(NU^A]IHSQ MUZYKALNYH U^EBNYH ZAWEDENIJs
Keywords: (NlIBRETTOs